Role Of Nutrition In Women With Recurrent Pregnancy Loss (International Journal of Food and Nutritional Sciences, 2023)
Recurrent pregnancy loss (RPL) is defined as two or more miscarriages or biochemical pregnancy losses (RPL). Since there is no recorded treatment for RPL, diet and drugs are implemented. A healthy-eating woman ideally gains around 10 kg of weight. Limiting salt intake is necessary. Caffeinated drinks should be used in moderation. Vegetables like broccoli, cabbage; milk derivatives, and fruits like bananas, mangoes, etc. are the most advisable foods. Pregnant women in rural areas are typically not well informed about the importance of consuming a healthy, balanced diet. Even modest, well-targeted awareness-raising campaigns should go a long way in ensuring maternal dietary diversity. With the help of proper nutrition and a diet plan, the rate and risk of miscarriage can be prevented and avoided. To reduce recurrent pregnancy loss, expectant mothers should get nutritional advice from dietitians, doctors, or other experienced mothers through personal meetings or social media platforms.